KAJIAN PARTISIPASI WANITA TANI DALAM PENGELOLAAN TANAMAN PADI SAWAH TERPADU DI KECAMATAN BUKATEJA KABUPATEN PURBALINGGA - Pujiharto Pujiharto; Watemin Watemin (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2008)
This research aimed to 1) learn profiles of women farmers who participate in the management of integrated crop for rice by observing age, formal education grade, farming effort, social economic grade, and farming experience, 2) know factors influencing women farmers participation in managing integrated crop of rice, and 3) know women farmers participation grade in managing integrated crop of rice in the relation with farmers rice effortproductivity and income. Bukateja District, Purbalingga Regency was chosen as the research region because of model region for having the management program. Thirty members of women farmers were chosen randomly. Result of the research showed that profiles of the women were different from the age rate, mostly between 31-40 years, formal education grade was mostly junior high school graduate, the way of doing farming effort was mostly by themselves, social economic grade was on medium rate, and the farming experience was mostly between 5 to 10 years. Factors influencing the participation were women farmers knowledge about the management, the age of women farmers, women farmers motivation, field’s size, and the intensity of counseling. By using McNemar test on 5% error rate, it was known that the participation rate in the program influenced the changes of farming effort productivity as well as farmers’ income with intensity from low to high. Key words : participation, women farmers, integrated crop management program for rice.